Development and evaluation of a national administrative code-based system for estimation of hospital-acquired venous thromboembolism in Ireland - Barry Kevane; Fionnuala Ní Áinle; Richard Daly; Ciara Kirke; Deirdre Lynch; Emer Gallagher; Therese Dalchan; Jacqui Curley; Ruth Buckley; Maeve P Crowley; Ann Marie O’Neill (BMJ Open)
Background Hospital-acquired venous thromboembolism (HA-VTE) is a significant patient safety concern contributing to preventable deaths. Internationally, estimating HA-VTE relies on administrative codes, in particular the International Classification of Disease (ICD) codes, but their accuracy has been debated. The Irish Health Service Executive (HSE) launched a National Key Performance Indicator (KPI) in 2019 for monitoring HA-VTE rates using the Australian Modification of ICD-10 (ICD-10-AM) codes.Objectives This study aims to (1) describe the development of the national HSE KPI and determine the national HA-VTE occurrence rate per 1000 discharges in 2022; (2) assess the contribution of each VTE ICD-10-AM code to the national HA-VTE figure; (3) estimate the positive predictive value (PPV) of the HSE KPI against true HA-VTE, in a single large tertiary (Irish Model 4) hospital.Methods A retrospective observational study used national data from Irish publicly funded acute hospitals, focusing on discharges from 2022. The HSE KPI was based on an assessment of HA-VTE as a rate per 1000 hospital discharges (as per the national metadata). Inclusion criteria were inpatient only, length of stay ≥2 days, age ≥16 years and non-maternity admission type (elective or emergency only). Maternity and paediatric hospitals were excluded.The PPV was determined through a detailed review of HA-VTE cases identified through the HSE KPI from April 2020 to October 2022 in a single large tertiary referral centre and determining the proportion indicating a true HA-VTE. Data analysis employed GraphPad Prism (Horsham, PA, USA).Results The national mean monthly HA-VTE rate was 11.38 per 1000 discharges in 2022. Pulmonary embolism (PE) without acute cor pulmonale (I26.9) was the most frequent contributor (59%). The mean PPV in the tertiary hospital was 0.37, with false positives attributed to acute illnesses, historical VTE coding errors and dual VTE diagnoses at admission.Discussion HA-VTE is a preventable cause of morbidity and mortality, necessitating accurate measurement. Administrative codes, while cost-effective and timely, reveal limitations in precision. This study identifies opportunities to improve code accuracy, address coding challenges and enhance the PPV.Conclusion This study provides valuable insights into estimated HA-VTE rates, the contribution of each individual ICD-10-AM code to the overall HA-VTE rate and the PPV of the measure. Ongoing refinement and quality enhancement are needed.